Cell Progression and Survival Functions of Enzymes Secreted in Extracellular Vesicles Associated with Breast and Prostate Cancers - Cosmos Ifeanyi Onyiba; Niwasini Krishna Kumar; Christopher J. Scarlett; Judith Weidenhofer (Cells)
Extracellular vesicles (EVs) are membrane-bound cargoes secreted by normal and pathological cells. Through their protein, nucleic acid, and lipid cargoes, EVs mediate several cellular processes, such as cell–cell communication, cell development, immune response, and tissue repair. Most importantly, through their enzyme cargo, EVs mediate pathophysiological processes, including the pathogenesis of cancer. In this review, we enumerate several enzymes secreted in EVs (EV enzyme cargo) from cells and patient clinical samples of breast and prostate cancers and detail their contributions to the progression and survival of both cancers. Findings in this review reveal that the EV enzyme cargo could exert cell progression functions via adhesion, proliferation, migration, invasion, and metastasis. The EV enzyme cargo might also influence cell survival functions of chemoresistance, radioresistance, angiogenesis, cell death inhibition, cell colony formation, and immune evasion. While the current literature provides evidence of the possible contributions of the EV enzyme cargo to the progression and survival mechanisms of breast and prostate cancers, future studies are required to validate that these effects are modified by EVs and provide insights into the clinical applications of the EV enzyme cargo in breast and prostate cancer.